The Impact of Attending Qur’an Memorization Programs on Psychological Wellbeing: A Study on Adult Females - Alnajashi, Sumyah Abdullah; Qasem, Mona Ahmad A. Al; Al-Mishaal, Kholoud Abdul Aziz; Aluthman, Wafa Abdullah Ebrahim (Islamic Guidance and Counseling Journal, 2025)
This research explored the effects of attending Qur'an memorization centers on major aspects of intact wellbeing and cognitive capabilities. The target population included four hundred healthy adult females (those Qur'an centers in the sample were female-only institutions, per the gender-segregated practices of many Muslim communities) classified into five groups according to their Qur'an level of memorization: (1) full memorization, (2) memorized 15–29 Juz’, (3) memorized 5–14 Juz’, (4) memorized 1–4 Juz’, and (5) minimal memorization limited to public schooling. They were instructed to complete a set of self-report scales and cognitive tests and a questionnaire on demographic information. A multivariate analysis of covariance showed an overall group difference in life satisfaction, happiness, and general reasoning, but not when examined individually with regard to statistical significance. Further analysis revealed that attendance at the Qur'anic memorization centers predicted life satisfaction more powerfully than happiness or cognitive abilities. In conclusion, these findings suggest that Qur'an memorization centers positively influence life satisfaction, while their influence on other cognitive and emotional factors may be more complicated. The current study indicates that the influence of religious practices on wellbeing should be considered and further research is required to examine the association between attendance at Qur'an memorization centers and the broad measures of cognitive functions.